Kepemimpinan Kolaboratif : Sebuah Bentuk Kepemimpinan Untuk Sekolah (Equilibrium: Jurnal Pendidikan, 2021)
Abstract. Changes that occur due to globalization need to be managed by leaders in order to achieve organizational goals. The way leaders manage change is influenced by the environment. Therefore, the style in leading an organization requires adaptation. Today, collaborative leadership is needed to cope with rapid change. Likewise the leadership of a school. The literature review method was chosen for the analysis of this study. Books, journals and other forms of publication are used as reference sources. This study provides an overview of collaborative leadership that needs to be applied in dealing with change for the success and effectiveness of schools, including for teachers and students.Keywords: Collaborative Leadership, Leadership, School Abstrak. Perubahan yang terjadi akibat globalisasi perlu dikelola pimpinan demi tercapainya tujuan organisasi. Cara pemimpin mengelola perubahan dipengaruhi oleh lingkungan. Oleh karena itu, gaya dalam memimpin suatu organisasi membutuhkan adaptasi. Saat ini, kepemimpinan kolaboratif dibutuhkan untuk mengatasi perubahan yang cepat. Begitu juga kepemimpinan suatu sekolah. Metode tinjauan literatur dipilih untuk analisis penelitian ini. Buku, jurnal maupun bentuk publikasi lainnya digunakan sebagai sumber referensi. Penelitian ini memberi gambaran  umum tentang kepemimpinan kolaboratif yang perlu diterapkan dalam menghadapi perubahan demi keberhasilan dan keefektifan  sekolah termasuk bagi guru dan siswa. Kata Kunci : Kepemimpinan Kolaboratif, Kepemimpinan, Sekolah
Keywords: Kepemimpinan Kolaboratif; Kepemimpinan; Sekolah